Breast MRI biopsy cancellation due to lesion nonvisualization. Issue 10 (13th September 2020) - Ambinder, Emily B.; Myers, Kelly S.; Mullen, Lisa A.; Di Carlo, Philip; Philip, Mary; Fragomeni, Roberto; Nguyen, Derek; Oluyemi, Eniola
Abstract: It is a clinical dilemma when a finding reported as suspicious on a breast MRI is not visualized at the time of a scheduled MRI‐guided breast biopsy. We retrospectively reviewed all canceled MRI‐guided biopsies at our institution between 6/1/2009 and 9/20/2019 and found a cancellation rate of 6.9% (72/1051). In one case, a mastectomy was performed after the canceled biopsy revealing a focus of DCIS in the same quadrant as the original finding (malignancy rate 2.1%). Our results support the current practice of 6‐month follow‐up MRI recommendation after a canceled MRI‐guided biopsy for lesion nonvisualization.